The Berenstain bears and the double dare - Berenstain, Stan, 1923-2005 (Berenstain, Stan, 1923-2005. First time books., 1988)
Brother Bear feels excited about joining Too-Tall Grizzly's gang until the members dare him to steal one of Farmer Ben's juicy watermelons.